Conflictual Accountability: Behavioral Responses to Conflictual Accountability of Agencies. Issue 8 (September 2021) - Schillemans, Thomas; Overman, Sjors; Fawcett, Paul; Flinders, Matthew; Fredriksson, Magnus; Laegreid, Per; Maggetti, Martino; Papadopoulos, Yannis; Rubecksen, Kristin; Rykkja, Lise H.; Salomonsen, Heidi H.; Smullen, Amanda; et al.
In contemporary public governance, leaders of public organizations are faced with multiple, and oftentimes conflictual, accountability claims. Drawing upon a survey of CEO's of agencies in seven countries, we explore whether and how conflictual accountability regimes relate to strategic behaviors by agency-CEO's and their political principals. The presence of conflictual accountability is experienced as a major challenge and is associated with important behavioral responses by those CEO's. This article demonstrates empirically how conflictual accountability is related to (a) controlling behaviors by principals, (b) constituency building behaviors by agencies, and (c) a general pattern of intensified contacts and information processing by both parties.